EMERGENCIES IN BUILDINGS CONSTRUCTED ON PILE FOUNDATIONS IN SUBSIDENT SOILS IN SOUTH RUSSIA - Boris F. Galay; Vitaly V. Serbin (Вестник Северо-Кавказского федерального университета, 2022)
The item offers a view on the first analysis of unsuccessful use of pile foundations in subsident loess soils in various cities of South Russia. The authors also provide definition of the issues related to pile constructions in subsident soils, as well as offer recommendations on resolving the issues.